EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN LEARNING STARTS WITH A QUESTION DAN THINK PAIR SHARE PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN BEKERJA SAMA SISWA KELAS VIII SMP NEGERI DI KABUPATEN KARANGANYAR - Susanti, Ika; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objectives of this research were to investigate: (1) which of the TPS-LSWQ learning model, the TPS learning model, and the direct learning model results in a better mathematics learning achievement; (2) which of the students with high, medium, and low team work have a better mathematics learning achievement; and (3) which of team work of the students result in a better learning achievement for each learning models; and (4) which of the TPS-LSWQ, TPS and direct learning models result in a better learning achievement for each level of team work of the students. This research used the quasi-experimental method. The population of this research was all students of the junior secondary schools in Karanganyar in the academic year of 2014/2015. The samples of this research consisted of 272 students who were divided into three experiment groups. The three groups consisted of group 1, group 2, and group 3. In each group 1,2, and 3 consisted of 90, 92, and 90 students. The data of this research were gathered from test of learning achievement in mathematics and questionnaire. The data were then analyzed by using unbalanced two-way analysis of variance. According to the research results, it can be concluded: (1) the learning model of TPS-LSWQ was better than that of the TPS and direct learning models while the learning model of TPS was better than the direct learning model; (2) the students with high team work had a better learning achievement than those with medium and low team work while the students with medium team work was better than the low team work; (3) in each team work, student with high team work, medium team work, and low team work, the mathematics learning achievement of the students taught with TPS-LSWQ learning model, TPS learning model, and direct learning model was as good as that of those; and (4) in TPS-LSWQ learning model, students with high, medium and low team work had the same achievement, the TPS learning model, students with high, medium, and low team work had the same achievement, the direct learning model, students with high and medium team work hadÂ  the same achievement, students with high team work had better achievement than low team work, and students with high team work had better achievement than low team work.Key words: TPS-LSWQ learning model, TPS learning model, direct learning model, team work and learning achievement.